SYSTEMIC APPROACH TO THE EVALUATION AND FORMALIZATION OF STRATEGIC ALTERNATIVES FOR THE INNOVATIVE DEVELOPMENT OF DAIRY PRODUCTION - VOLOSHCHUK, Maksym; PRUSOVA, Galina (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article explores a systematic approach to assessing and formalizing strategic alternatives for innovative development of dairy enterprises. The intensification of globalization substantiates the relevance of the issue, the growing demands for product quality and safety, and the digitalization of the agro-industrial complex (AIC). It is determined that modern dairy production operates in conditions of intense competition, high resource prices, climate risks, and rapidly changing consumer preferences, requiring enterprises to adopt integrated strategic management approaches. The essence of the systemic approach is revealed through its integration of the economic, organizational, technological, and environmental aspects of managing innovation processes, and through its focus on going beyond local or purely technical modernizations. Special attention is paid to the formalization of strategic alternatives, which is based on strategic analysis methods, digital data processing tools, and forecasting models. The concept of a “roadmap” for the innovative development of dairy production is proposed, which includes the following stages: diagnostics of the initial state of the enterprise, identification of strengths and weaknesses, formation and testing of pilot projects, scaling of successful practices, entry into markets with value-added products, and organization of a system of continuous improvement. It is proven that such an approach allows integrating innovations into production and economic processes, reducing uncertainty and increasing flexibility to respond to external challenges. It is emphasized that using a systemic approach in combination with digital analytics tools (Big Data, demand forecasting models, and artificial intelligence) to optimize production processes creates additional opportunities to accurately assess the effectiveness of alternative strategies, thereby increasing the economic performance and competitiveness of dairy enterprises. The article emphasizes that implementing a systemic approach contributes to the formation of a sustainable trajectory of dairy production development in Ukraine, meets the principles of sustainable development, and ensures integration into global agri-food chains.